2005
DOI: 10.5424/sjar/2005033-156
|View full text |Cite
|
Sign up to set email alerts
|

Induction of fruit calcium assimilation and its influence on the quality of table grapes

Abstract: Sprays containing soluble Ca, polypeptidic N and Ti ascorbate in several combinations were applied to cv. Crimson table grape vines (Vitis vinifera L.). Foliar spraying resulted in the accumulation of N, P, K, Ca, Mg, Fe, Zn, Cu and Ti in the leaves, but not of Na, Cl or Mn. In the berries, Ca, Fe, Zn and Cu concentrations increased in the skin and flesh. These berries were also larger than controls, firmer, had a deeper external red colour, and their weight loss during postharvest storage was reduced. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Consumers' perception of berry quality and preference is most likely defined by TSS, which correlates to ripeness of the berry. Concentration of TSS and pH in ‘Crimson seedless’ and ‘Sugraone’ are comparable to that reported by various authors …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consumers' perception of berry quality and preference is most likely defined by TSS, which correlates to ripeness of the berry. Concentration of TSS and pH in ‘Crimson seedless’ and ‘Sugraone’ are comparable to that reported by various authors …”
Section: Discussionsupporting
confidence: 88%
“…The concentrations of mineral elements analyzed for both ‘Crimson seedless’ and ‘Sugraone’ were within the range reported by Esteban et al ., Alcaraz‐Lopez et al ., and Grembecka and Szefer (Tables and ). The concentration of sodium was similar to that reported by Esteban et al ., Alcaraz‐Lopez et al ., and Grembecka and Szefer for ‘Crimson seedless’ but sodium concentration was almost one order of magnitude higher in ‘Sugraone’ (Table ), irrespective of treatment. Concentrations of iron, zinc, and manganese in this study were about ten times higher than those reported by Grembecka and Szefer for red and white table grapes in Poland.…”
Section: Discussionmentioning
confidence: 93%
“…The growth of bush bean plants was not significantly different when leaf Ti contents varied from 1.2 to 11.7 mg kg −1 (Wallace et al, 1977 ). Table grape ( Vitis vinifera L.) plants were healthy with a mean Ti content of 17.8 mg kg −1 in leaves (Alcaraz-Lopez et al, 2005 ). Oilseed rape plants grew healthily with Ti content in shoots ranging from 16.8 to 66.7 mg kg −1 during their flowering period (Kovacik et al, 2016 ).…”
Section: Ti Improves Plant Performancementioning
confidence: 99%
“…Pre-veraison calcium applications significantly affected fruit mechanical characteristics as shown by higher values of flesh firmness and berry breaking force and lower B. cinerea rots during storage thus maintaining postharvest fruit quality (Ciccarese et al, 2013). Calcium applications during the first stages of fruit development induce an increase of the final berry size (Alcaraz-Lopez et al, 2005).…”
Section: Fertilization and Soil Management (Table Grapes)mentioning
confidence: 99%